Measuring the performance of Malaysian universities using Charnes, Cooper and Rhodes (CCR) and slack-based measure (SBM) models - Norfarziah Adna; Nazhatul Sahima Mohd Yusoff; Nor Syafiqah Azwani Rosly; Nur Syafiqah Izati Ahmad Marzuki; Wan Nur Amira Balqis Wan Razali (Penerbit Universiti Kebangsaan Malaysia, 2022)
The efficiency and productivity of the higher education sector play an important role in the development and growth of a nation, both as a major source of human capital and the main driver of the country’s economic growth. Public higher education is under tremendous pressure worldwide to improve its performance and quality. This paper examines the efficiency scores of 20 public universities in Malaysia using the Charnes, Cooper, and Rhodes model (CCR) and Slack-Based Measure model (SBM). Three inputs and five outputs are determined to measure the performance of the university through the graduate student’s marketability. The findings show that out of 20 public universities, 11 public universities are efficient with an efficiency score equal to 1. Meanwhile, the remaining nine public universities showed inefficient score results. Suggestions and improvements are identified to improve the efficiency of those universities in the future. To overcome the inefficient universities, the use of the SBM model provides recommendations to consider in measuring efficiencies which are number of postgraduate students enrolled, number of undergraduate students enrolled, and number of academic staff as the inputs and number of postgraduates, number of undergraduates, number of graduates working, number of graduates who choose to further studies and number of graduates choose to develop skills as the outputs. All the criterias need to consider for the improvement for the universities to be more efficient.